The Formation of a Religious Culture in Enhancing Spiritual Intelligence among Middle School Students in Indonesia - Abdul Hamid; Khozin Khozin; Rahmad Hakim (KURAS Institute, 2025)
This study aims to describe how the formation of religious culture in the school environment can enhance the spiritual intelligence of students, with a case study at SMP Negeri 1 Sumberasih, Probolinggo Regency. This study uses a qualitative approach with a case study method, involving observation, in-depth interviews, and documentation as data collection techniques, followed by data analysis through the stages of data reduction, data display, and conclusion drawing. The validity of the data was ensured using triangulation of sources and methods to maintain the credibility and reliability of the findings. The results show that religious culture in schools is manifested through activities such as congregational prayers, Quran recitation, sunnah fasting, greetings and salutations, as well as istighasah and communal prayers. This culture tangibly shapes religious attitudes, strengthens spiritual awareness, and improves the quality of students' relationships with God, fellow human beings, and the environment. Factors supporting the successful formation of religious culture include teacher role modeling, school leadership support, parental involvement, and a conducive social environment. This study recommends a broader exploration of the relationship between religious culture and other aspects of student development, such as emotional intelligence, social character, or leadership values.